Nation Branding of Developing Countries - Sendrea, Veronica (2014)
This Master's thesis focuses on nation branding in developing countries. Nation branding is an emerging discipline that aims to build and improve a nation's image through the application of marketing techniques. The aim of the thesis is to contextualize the nation branding of developing countries within the broader framework of the theory and practice of nation branding and development studies. The thesis is structured into three chapters. The first chapter offers an introduction into the theory and practice of nation branding and the critique attached to it. The second chapter then looks at how nation branding fits into the wider context of development studies, and the scale of its relevance for developing countries with a special focus on its application for export, FDI and tourism promotion and its significance in development co-operation. The last chapter is dedicated to case studies of application of nation branding in two developing countries: Uruguay and Thailand. The conclusion sums up the results.